"There is still a perception that homelessness is a housing problem": devolution, homelessness and health in the UK. Issue 2 (6th June 2016) - Whiteford, Martin; Simpson, Glenn
Abstract : Purpose: The purpose of this paper is to provide an exploratory account of the links between devolution, homelessness and health in the UK. Specifically, it focusses on the policy context and governance structures that shape the systems of healthcare for homeless people in London, Scotland, Wales and Northern Ireland. Design/methodology/approach: Empirically the paper draws on semi-structured interviews with a small sample of policy and practice actors from the devolved territories. Qualitative interviews were supplemented by a comparative policy analysis of the homelessness and health agenda within the devolved regions. Theoretically, it takes inspiration from Chaney's concept of the "issue salience of homelessness" and explores the comparative character of healthcare as pertains to homeless people across the devolved territories. Findings: The paper provides clear evidence of areas of divergence and convergence in policy and practice between the devolved regions. These features are shown to be strongly mediated by the interplay of two factors: first, the scope and scale of national and local homelessness prevention strategies; and second, intra-national variation in public health responses to homelessness. Originality/value: The paper offers considerable insight from a comparative policy perspective into the nature of healthcare provision for homeless people in the devolved regions.